The Effect of Material Flow Cost Accounting on Environmental Performance with Green Accounting as a Moderator - Iwan Christian; Glenn Andrenossa; Theresia Octaviani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
The aim of this research is to determine the effect of Material Flow Cost Accounting on Environmental Performance with Green Accounting as a moderating variable. This research uses a quantitative type of research using a purposive sampling method as data analysis. This research uses secondary data in the form of documentation obtained on websites, namely the company's annual report ( Annual Report ), financial report ( Financial Report) and sustainability report ( Sustainability Report ) obtained from the Indonesian Stock Exchange website and the websites of the companies that is the research sample. The number of mining companies included in the research sample criteria is 12 companies listed on the Indonesia Stock Exchange with the observation year 2015-2020. The results of this research show that Material Flow Cost Accounting does not have a significant positive effect on Environmental Performance. Meanwhile, Green Accounting as a moderating variable cannot strengthen the relationship between Material Flow Cost Accounting and Environmental Performance. The capability of the regression model is that only 11.7% of the variation in the value of the Environmental Performance variable can be explained by variations in the independent variables, while the remaining 88.3% is influenced by other variables not examined by this research.